INDIVIDUO Y COMUNIDAD: REFLEXIONES SOBRE EL ETERNO CÍRCULO FICHTEANO - López-Domínguez, Virginia (Daimon Revista Internacional de Filosofia, 1994)
This article shows that Fichte's defense of individuality (the most radical among the idealist) descend from the illustrated problematic which, after kantian framing, changes to the question of how to maintain the individual freedom opposite to the absolut. Fichte resolves this trouble in the GWL: a) admising the indeducibility and irrationality of the second principle and accepting it from the practice point of view; b) avoiding to turn the absolute I into metaphysic hypothesis, and this is the reason of his refusal to use the term «intellectual intuition»; c) converting the begining of the particular human life (Anstoss) in a factum which doesn't admit further explanation. As result of this, the representation genesis will be expressed in solipsistic terms, though the faith which Fichte refers to is a moral one, that goes in first place to the intelligible other intersubjetive world. Also, after this monodism continues necessarily the socialization of the I by means of the material community that appears in GNR, where the body is considered as meeting point of human being.